2015
DOI: 10.1007/s10803-015-2578-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Sensory Reactivity in Autism Spectrum Disorder: Application and Simplification of a Clinician-Administered Sensory Observation Scale

Abstract: Sensory reactivity is a new DSM-5 criterion for autism spectrum disorder (ASD). The current study aims to validate a clinician-administered sensory observation in ASD, the Sensory Processing Scale Assessment (SPS). The SPS and the Short Sensory Profile (SSP) parent-report were used to measure sensory reactivity in children with ASD (n = 35) and typically developing children (n = 27). Sixty-five percent of children with ASD displayed sensory reactivity symptoms on the SPS and 81.1 % on the SSP. SPS scores signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 37 publications
6
51
0
Order By: Relevance
“…This finding is similar to previous work showing moderate agreement between a sensory questionnaire and direct observation [15], [36]. Tavassoli et al (2016) found an inter-rater agreement between questionnaire and observation of 74%, however, general sensory processing was evaluated rather than auditory and tactile over-responsivity [36]. Schoen et al (2008) focussed on SOR and reported a moderate correlation of .47, similar to our findings [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is similar to previous work showing moderate agreement between a sensory questionnaire and direct observation [15], [36]. Tavassoli et al (2016) found an inter-rater agreement between questionnaire and observation of 74%, however, general sensory processing was evaluated rather than auditory and tactile over-responsivity [36]. Schoen et al (2008) focussed on SOR and reported a moderate correlation of .47, similar to our findings [15].…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the agreement between SSP and SP-3D:A for AOR was 65% and TOR was 50%. This finding is similar to previous work showing moderate agreement between a sensory questionnaire and direct observation [15], [36]. Tavassoli et al (2016) found an inter-rater agreement between questionnaire and observation of 74%, however, general sensory processing was evaluated rather than auditory and tactile over-responsivity [36].…”
Section: Discussionsupporting
confidence: 90%
“…Similar sensory system deficits are also seen in humans with FXS (Baranek et al, 2008; Castrén et al, 2003; Frankland et al, 2004; Kogan et al, 2004; Miller et al, 1999; Rotschafer and Razak, 2014; Schneider et al, 2013; Van der Molen et al, 2012a,b). The symptoms can be evaluated by clinical assessment or parent report (Baranek et al, 2008; Ben-Sasson et al, 2007; Tavassoli et al, 2016) and have recently been included as a criterion for ASD diagnosis in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5). Sensory abnormalities in ASD and FXS are not only among the most replicable features of these disorders (Ben-Sasson et al, 2008; Donkers et al, 2015; Klintwall et al, 2011; Liss et al, 2006), they are also present early in childhood (Baranek et al, 2008; Elison et al, 2013; Elsabbagh et al, 2013; Germani et al, 2014; Zwaigenbaum et al, 2005) and are strong predictors of some later-emerging symptoms, such as anxiety (Green et al, 2012; Sullivan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The SPS was originally developed for children with Sensory Processing Disorder and identifies sensory hyperreactivity, hyporeactivity or seeking behaviors in children and adults [Schoen, Miller, & Green, 2008]. The measure was recently validated in children with ASD [Tavassoli et al, 2016]; however, the SPS requires children to respond to verbal instructions to carry out various tasks, and thus adequate receptive language abilities are necessary. The SIPT offers 17 different tasks assessing perceptual abilities within visual, tactile, kinesthetic, and motor domains for children between the ages of 4 and 8.…”
Section: Introductionmentioning
confidence: 99%